Relevansi Studi Integrasi Islam, Sains, dan Budaya Nusantara dalam Pendidikan Islam di Era Global - Emi Hariyanti; Moh. Roqib (Transformasi Manageria Journal of Islamic Education Management, 2024)
Information technology (ICT) from internet-connected mobile phones has changed learning models, culture, social life, imagining the future and political participation. With changes in social attitudes and community psychology, education must experience a revolution that demands new ways of mastering science in learning. Islamic education has so far made changes in models, methods and strategies to develop Islamic education to be modern and adapt to global situations and conditions. And stay within the corridor of educational ideals and goals based on the Quran and Hadith, as well as the goals of national education, the principles and philosophy of the country. Adhering to the principle of keeping good traditions and adopting new and better traditions is a paradigmatic mantra of progress, continuity, openness to innovation to achieve knowledge transfer. Therefore, this paper aims to analyze the role of Islamic integration studies, science, and archipelago culture in the global era. This writing uses a literature study approach, using books related to the topic under study as sources and research materials. Integrating Quranic values into the Islamic education system, in the context of paradigm-shifting phenomena and modern digital culture, is an inevitable logical consequence of science and information technology is absolutely necessary. This can be achieved through various approaches such as curriculum innovation, character building, creation of an educational environment and strengthening of human resources and role models.